Characteristics of Carotid Artery among Ischemic Heart Disease Patients with or without Diabetes Mellitus (Journal of Current and Advance Medical Research, 2023)
Background: Involvement of coronary artery can vary among the ischemic heart disease patients with or without diabetes mellitus.Objective: The purpose of the present study was to assess the characteristics of carotid artery among ischemic heart disease patients with or without diabetes mellitus.Methodology: This case-control study was conducted in the Department of Cardiology at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. The study was carried out from July 2003 to June 2005 for a period of two years. Patients who had coronary artery diseases or ischemic heart diseases and diabetes mellitus undergoing coronary angiography were selected as case of this study. In control group, age, sex match patients of IHD undergoing CAG not having DM were included. Every patient was clinically examined by detailed history and physical examination during entry into study. ECG, chest X-ray, echocardiogram, blood sugar (fasting), blood 2 hrs. after 75gm of glucose and or breakfast were analyzed. Coronary angiography was done in all patients through femoral approach by modified Seldinger technique. Carotid arteriography was performed selective and nonselective method by Hunter head or right Judkin's catheter in standard AP, lateral and oblique views.Results: A total number of 100 patients were included in this study. Of them 50 patients were coronary artery disease with diabetes mellitus and another 50 patients were coronary artery disease without diabetes mellitus. Morphological character of the lesion was also assessed. The mean age was found 57.48 years with 6.04 standard deviation (SD) in DM and 55.64 years with 6.34 standard deviation in NDM group and also 56.56 years with 6.49 standard deviation in the whole study population. The value of unpaired t-test was 0.158 and it was insignificant (p>0.05). The common site of lesion was bifurcation, internal carotid, common carotid and external carotid artery which were 13 cases, 9 cases, 4 cases and 1 case respectively. The individual vessel involvement was 9(18.0%) cases in right, 6(12.0%) cases in left, and 3(6.0%) cases in both in DM group whereas 5 (10.0%) cases in right, 3(6.0%) cases in left, and 1(2.0%) case in both in NDM group. It observed that out of 100 study subjects 10 had complex carotid lesion in DM and 4 in NDM.Concussion: In conclusion the common site of lesion was bifurcation and internal carotid artery mostly in right side.Journal of Current and Advance Medical Research, January 2023;10(1):7-12